What Enables and Sustains Corruption in African Universities? - Jansen, Jonathan (International Higher Education, 2023)
Corruption in universities is not something new. But what happens when corruption becomes endemic to institutional life? What sustains the corrupt practices that lead to chronically unstable universities? This article describes the operations of two important concepts that explain ongoing corruption in African universities: institutional capability and institutional integrity.